CURRENT STUDIES IN THERMOREGULATION - Alfredo Jesús López Dávila (Pensar en Movimiento)
The aim of this review is to present recent advances in the understanding of the physiological mechanisms of thermoregulation in mammals, which can be divided into two types including reflex (or autonomic) and behavioral thermoregulation. In reflex thermoregulation, which is totally beyond the voluntary control of the individual, thermoreceptors detect thermal stimuli. Afferent pathways transport information sensed by receptors to the hypothalamus, with relays in the spinal cord and the midbrain. The hypothalamic integration center coordinates its response to the thermal stimuli and sends neural signals through efferent pathways with relays in the medulla and the spinal cord. These signals finally reach effectors that are capable of conserving or dissipating thermal energy in order for body temperature to remain constant. Today, a growing body of evidence suggests considerable physiologic integration between reflex thermoregulation, energy balance and metabolism, which makes considering manipulation of reflex thermoregulation a potential strategy in order to treat metabolic conditions or influence body composition. In behavioral thermoregulation, which relies on voluntary decisions, thermal stimuli are detected by the same receptors. Afferent pathways transport thermal information to the spinal cord, thalamus and cerebral cortex, which influences the perception of thermal comfort and the decisions of the individual in order to gain or lose heat. The recent findings have also brought new questions that are discussed at the end of this review.